2009
DOI: 10.1590/s1516-89132009000700026
|View full text |Cite
|
Sign up to set email alerts
|

The effect of management of transport and lairage conditions on broiler chicken breast meat quality and DOA (Death on Arrival)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 11 publications
5
22
0
6
Order By: Relevance
“…At a current of 40 V and frequency of 1000 Hz, they observed that 90% of animals were stunned and blood loss was maximized. Furthermore, additional studies demonstrated that stressful conditions just before preslaughter activities promoted the development of PSE (pale, soft, exudative) meat (Mitchell and Kettlewell, 1998;Barbut et al, 2008;Oba et al, 2009). This was shown to be caused by the rapid decline of pH values while the carcass is still warm; thus, leading to the denaturation of myofibrillar proteins (Olivo et al, 2001, Barbut, 1997 and loss of their functional properties (Kissel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…At a current of 40 V and frequency of 1000 Hz, they observed that 90% of animals were stunned and blood loss was maximized. Furthermore, additional studies demonstrated that stressful conditions just before preslaughter activities promoted the development of PSE (pale, soft, exudative) meat (Mitchell and Kettlewell, 1998;Barbut et al, 2008;Oba et al, 2009). This was shown to be caused by the rapid decline of pH values while the carcass is still warm; thus, leading to the denaturation of myofibrillar proteins (Olivo et al, 2001, Barbut, 1997 and loss of their functional properties (Kissel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Para corroborar com esses resultados, Oba et al (2009), verificaram que em condições dramáticas, no período mais quente do dia (33 o C), sem banho e transportados somente `a baixa velocidade, em estradas de terra, por período de 180 minutos e descanso ao abate de 90 minutos, foram altamente susceptíveis ao estresse térmico, provocando maior mortalidade, chegando ao máximo de DOA, de 57,0%.…”
Section: Resultsunclassified
“…Most studies have correlated long-term transport with higher mortalities [3,[11][12][13][14]. Aral et al found that for broiler chickens transported for slaughter in Turkey, mortality rates ranged from 0.29% in journeys lasting less than 2 h to 0.46% for journeys lasting more than 10 h [11].…”
Section: Transport Durationmentioning
confidence: 99%